Mental health nurses' experience of challenging workplace situations: A qualitative descriptive study - Cranage, Kylie; Foster, Kim (International journal of mental health nursing, 2022)
Mental health nursing is acknowledged internationally as being a demanding profession; however, little is known about the range of experience and complexity of workplace challenges or their impacts on mental health nurses (MHN). This qualitative descriptive study aimed to examine and describe the range of challenging workplace situations experienced by MHN and is reported according to the Standards for Reporting Qualitative Research. An online cross‐sectional survey collected demographic data and open‐ended descriptions of workplace challenges experienced by n = 374 Australian MHN. Using a modified a priori framework, four categories of experience were derived through content analysis: consumer‐related, colleague‐related, nursing role‐related, and organizational service‐related challenges. Many accounts described a complex interplay of challenges. The findings extend prior knowledge on MHN experiences. Frequent workplace challenges included violence and aggression from consumers, bullying from colleagues, low staffing levels, and poor skill mix. Further extending the evidence, key challenges rarely described in prior literature were the psychological impacts of suicides and murder; the personal nature of threats from consumers; moral distress and concerns with colleagues' quality of practice; and exacerbation of practice‐related issues by lack of support from colleagues and/or the organization. These have important implications for the profession and can inform targeted strategies to reduce stressors where possible, build staff well‐being, support workforce retention, and improve the provision of quality care. The implementation of targeted policy and initiatives that focus on reducing key stressors and supporting practice are vital to staff retention and ensuring a high standard of practice in complex mental health workplaces.